2010
DOI: 10.1161/circulationaha.109.933275
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Aggressive Decongestion During the Treatment of Decompensated Heart Failure on Renal Function and Survival

Abstract: Background-Overly aggressive diuresis leading to intravascular volume depletion has been proposed as a cause for worsening renal function during the treatment of decompensated heart failure. If diuresis occurs at a rate greater than extravascular fluid can refill the intravascular space, the concentration of such intravascular substances as hemoglobin and plasma proteins increases. We hypothesized that hemoconcentration would be associated with worsening renal function and possibly would provide insight into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
470
4
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(526 citation statements)
references
References 39 publications
28
470
4
24
Order By: Relevance
“…According to a previous study, the renal impairment in HF patients is associated with poor prognosis 21. However, some recent studies suggested that the beneficial effect of aggressive decongestion during treatment persisted after hospital discharge in HF patients with and without worsening renal function 7, 8. We observed that both serum creatinine and BNP were higher in the HD group than in the LD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, the renal impairment in HF patients is associated with poor prognosis 21. However, some recent studies suggested that the beneficial effect of aggressive decongestion during treatment persisted after hospital discharge in HF patients with and without worsening renal function 7, 8. We observed that both serum creatinine and BNP were higher in the HD group than in the LD group.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, loop diuretics are prescribed in 70–90% of patients with chronic HF 3, 5, 6. Some studies showed that aggressive decongestion had a beneficial effect on survival in these patients 7, 8. However, other studies have suggested that high‐dose loop diuretics were associated with poor prognosis in HF patients 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, several retrospective analyses from completed trials have suggested that it may be important to consider the time course of WRF and the relationship of WRF to the degree of decongestion achieved, but even in those analyses, the best outcomes are clearly in those patients who achieve clinical decongestion while preserving renal function. [8][9][10] Until a prospective trial clearly establishes that any form of WRF is safe during treatment of AHF, it is reasonable to assume that the goal of treatment should be adequate clinical decongestion without causing renal dysfunction (or worsening it if already present). Because reliance on changes in serum creatinine does not distinguish among the various causes of WRF, and because it may be important in particular to know whether true acute kidney injury occurs, the use of new biomarkers, such as cystatin C, KIM 1 (kidney injury molecule-1), and urinary natriuretic peptides, may lead to enhanced understanding of the nature and implication of mechanisms underlying WRF in future trials.…”
mentioning
confidence: 99%
“…Furthermore, bolus infusions do not promote gradual diuresis and therefore do not allow time for the fluid in the periphery to move from the extravascular to the intravascular space, which leads to intravascular volume depletion and significant drops in renal perfusion, subsequently leading to renal dysfunction 23. Aggressive decongestion therefore leads to transit renal dysfunction during the acute phase of AHF; however, current research suggested that transient renal dysfunction with the use of high‐dose diuretics was associated with early clinical improvement and not a poor outcome 23, 24. It was reported recently that some mechanisms of the renal dysfunction were not associated with an adverse outcome in patients with AHF.…”
Section: Discussionmentioning
confidence: 99%